Economical and ecological efficiencies of energy saving technology in wheat production - Jalbiidandariin, Suvdaa (Mongolian Journal of Agricultural Sciences, 2014)
Energy saving technologies in wheat production are necessitated by nowadays requirements. Research revealed the minimum tillage is the most economical and ecological efficient technology in wheat production in Mongolia. Therefore, structure of technical park should to be changed through government policy. DOI: http://dx.doi.org/10.5564/mjas.v11i2.235 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.138-141